2020
DOI: 10.1080/16549716.2020.1831794
|View full text |Cite
|
Sign up to set email alerts
|

Implementing effective eLearning for scaling up global capacity building: findings from the malnutrition elearning course evaluation in Ghana

Abstract: Background: Global demand for capacity building has increased interest for eLearning. As eLearning resources become more common, effective implementation is required to scale up utilization in Low-and Middle-Income Countries (LMICs). Objective: This paper describes the process of implementing a malnutrition eLearning course, effectiveness of course delivery models devised, factors affecting course completion, and cost comparison between the models and face-to-face training at healthcare and academic institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…The same review reported that evaluations, in general lacked standardization, especially regarding the tools, and only face-to-face initiatives were evaluated in the long term beyond the individual level ( 23 ). Many evaluations are restricted to knowledge assessment through pre-and post-tests, which are indicative but limited ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same review reported that evaluations, in general lacked standardization, especially regarding the tools, and only face-to-face initiatives were evaluated in the long term beyond the individual level ( 23 ). Many evaluations are restricted to knowledge assessment through pre-and post-tests, which are indicative but limited ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the academic institutions, course completion rates and knowledge gained were higher where the course was integrated as a required element of the curriculum. 26 Six institutions integrated the course into teaching within 12 months. Currently, all 7 academic institutions are using the course.…”
Section: Ghana Country Studymentioning
confidence: 99%
“…Delivering eLearning is less costly than face-to-face teaching. 26 Whichever approach is chosen, training must be integrated within routine government programs as it is important in designs for implementation, sustainability, and scale-up.…”
Section: Capacity-building Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies used grades from assessment tasks and final exams on two or more occasions to assess student knowledge (7; e.g., Annan et al, 2020). However, these articles did not discuss the value of the metrics used in their assessments or exams.…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%